2005
DOI: 10.1055/s-2004-830491
|View full text |Cite
|
Sign up to set email alerts
|

Responses of N-Terminal Pro-Brain Natriuretic Peptide (NT-proBNP) and Cardiac Troponin I (cTnI) to Competitive Endurance Exercise in Recreational Athletes

Abstract: The present study was designed to investigate whether the stress of a half-marathon race can induce myocardial cell injury or left ventricular dysfunction in moderately trained runners of both gender, as assessed by post-race plasma concentrations of biochemical cardiac-specific markers and by quantitative echocardiographic measurements. We examined 12 male (mean+/-SD); age: 42.8+/-7.3 yr; height: 177.6+/-7.4 cm; body mass: 75.6+/-9.4 kg; BMI: 24.1+/-1.8 and 13 female (mean+/-SD); age: 39.0+/-6.5 yr; height: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 37 publications
2
40
2
Order By: Relevance
“…Measurement of NT-proBNP before and immediately after strenuous exercise can help to distinguish individuals with and without myocardial ischemia with a high degree of accuracy (18). Previous studies have shown that NT-proBNP levels may also increase significantly in healthy male athletes after strenuous exercise as a response to ventricular volume expansion (19)(20)(21). However, owing to the moderate workload applied in our study, no significant increases in this marker were observed.…”
Section: Discussioncontrasting
confidence: 48%
“…Measurement of NT-proBNP before and immediately after strenuous exercise can help to distinguish individuals with and without myocardial ischemia with a high degree of accuracy (18). Previous studies have shown that NT-proBNP levels may also increase significantly in healthy male athletes after strenuous exercise as a response to ventricular volume expansion (19)(20)(21). However, owing to the moderate workload applied in our study, no significant increases in this marker were observed.…”
Section: Discussioncontrasting
confidence: 48%
“…Several recent reports have demonstrated myocardial dysfunction after endurance physical activity [2], [3], [5], [7], [8], [21], [22], [23], [24]. Most of these studies demonstrated transient cardiac dysfunction manifested as left ventricular systolic and diastolic abnormalities as well as right ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated transient left and right ventricular systolic and diastolic dysfunction [1], [2], pulmonary hypertension, and abnormally elevated levels of cardiac biomarkers such as brain natriuretic peptide (BNP) and troponin following endurance exercise [3], [4], [5], [6], [7], [8]. There was a positive correlation between the intensity of the endurance activity and the level of cardiac abnormalities developed.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are assumed to indicate cardiac injury or dysfunction [5,18] since troponin T and troponin I are highly specific markers of myocardial cell damage, even in the presence of simultaneous skeletal muscle damage [16]. Furthermore significant cardiac stress leads to an elevation of these biomarkers even in absence of obstructive coronary disease [1].…”
Section: Introductionmentioning
confidence: 99%
“… Prolonged strenuous exercise leads to an elevation of cardiac specific biomarkers such as troponin T (TnT), troponin I (TnI), MB-creatine kinase (CKMB) and N-terminal pro brain natriuretic peptide (NT-pro BNP) in apparently healthy endurance athletes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. These parameters are assumed to indicate cardiac injury or dysfunction [5,18] since troponin T and troponin I are highly specific markers of myocardial cell damage, even in the presence of simultaneous skeletal muscle damage [16].…”
Section: Introductionmentioning
confidence: 99%